Laser Dust Logging of the South Pole Ice Core (SPICE) - Bay, Ryan (IEDA: US Antarctic Program Data Center, 2019)
We deployed an oriented laser dust logger in the SPICEcore borehole in order to study the particulate stratigraphy, volcanology, glaciology and climatology of South Pole. We obtained a detailed record of dust and ash, SPICEcore age versus depth, and measurements of the optical anisotropy indicated by IceCube analyses.